Indonesia - Retno Wigajatri Purnamaningsih; Dini Marhaeni Elecevani (Jurnal Penelitian Pendidikan IPA, 2022)
Electrosurgery Unit (ESU) is a medical surgical device that uses high frequency and high voltage with the aim that the patient does not experience excessive bleeding during the operation process. The development of electrosurgery unit technology evolves over time from monopolar to bipolar. However, in the development of the use of the tool, monopolar technology is always the most widely used in tissue surgery techniques. For this reason, this research was determined to use only the Monopolar principle. In Electrosurgery, the actual unit only uses one frequency selection, by changing (increasing or decreasing) the power value. With cases like this sometimes the user or equipment users will always change the power value during operation to determine the right power value. In this case, the author tries to make a prototype of an electrosurgery device with a frequency that can be selected (300, 350, 400, 450, 500, 550, 600 and 650 KHz) with a fixed power. By examining the results of the effectiveness of cutting (CUT) on tissue samples. It is hoped that it will be known which one is faster and more effective which can be used in cutting techniques (CUT) in surgery